The family and the values of family life in the social science of the Catholic Church - analysis of selected sources - Frączek, Zofia (Kwartalnik Naukowy Fides et Ratio, 2022)
The aim of this text is to show the place of the family and related values of family life (such as e.g. marriage, child, mother, father, senior citizen), in the Social Science of the Catholic Church. A qualitative analysis of selected sources has been made, including documents of synods and councils, papal encyclicals and other statements of popes. Some monographs and scientific articles, thematically related to the subject, were also used, including electronic sources. The source materials analysed show the great commitment of the Catholic Church in proclaiming the truth about the family and in shaping the social awareness of its value, as well as the value of marriage as the basis of the family community and of the mother (wife) and father (husband), who are the guardians and guides of the child in life. The Church also draws attention to the value of the child and the need to protect its rights, placing it at the forefront of social and family life, especially sick children, disabled children, children deprived of parental care, victims of war and cataclysms. It attaches great importance to the elderly generation, which acts as a witness to the past and as a source of wisdom for the young, as well as a link between generations and a safeguard for the continuity of the family. Despite the ongoing changes in the Social Science of the Catholic Church, its constant concern for the family and the values connected with it can be visible.